Relationship Between Leaf Nutrient Concentrations with Fruit Yield and Quality of Pummelo (Citrus maxima (Burm.) Merr.) in Nghe An Province, Vietnam - Hien Huu Nguyen; Minh Xuan Tran; Toan Nguyen Tai (Universitas Sebelas Maret, 2026)
Pummelo is a high-value cash crop in Vietnam, where optimizing cultivation practices requires a profound understanding of the correlations between leaf nutrient concentrations and fruit quality.This study investigated the correlations between leaf nutrient levels and the yield and quality of the ‘Quang Tien pink’ pummelo cultivar. The research was conducted in 2024 across 25 pummelo orchards in Nghe An Province. Leaf samples were analyzed for concentrations of N, P, K, Ca, Mg, Zn, Mn, Cu, and Fe. Fruit characteristics evaluated included fruit weight, circumference, peel thickness, edible portion, juice volume, juice pH, total soluble solids (TSS), titratable acidity (TA), and the TSS/TA ratio. The findings demonstrated that foliar N, P, and K concentrations were significantly and positively correlated with fruit circumference, fruit weight, juice volume, TSS, juice pH, and TA. In contrast, P and K levelswere negatively correlated with peel thickness (r = -0.639, -0.906, respectively). Leaf Ca concentration was positively correlated with peel thickness (r = 0.537) but negatively associated with fruit weight (r = -0.406) and TSS (r = -0.404). Additionally, Zn, Cu, Fe, and Mn concentrations showed significant positive correlations with TSS (r = 0.723, 0.660, 0.443, and 0.570, respectively), while Zn and Cu were negatively correlated with peel thickness (r = -0.539, -0.456, respectively). These results establish a robust scientific baseline for precision nutrient management strategies to maximize the yield and fruit quality of pummelo.